PERLAKUAN AKUNTANSI ASET BIOLOGIS BERDASARKAN PSAK NOMOR 69 PADA PT ASTRA AGRO LESTARI, TBK - B1033131004, Arie Wijaya Anthony (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
This research aims to know the difference in recognition and measurement of biological assets in palm plantation before and after the application of PSAK 69, and to know the impact of implementation fair value on biological asset in the financial statements. This research was conducted using qualitative descriptive comparative analysis through a case study on one of the plantation companies listed on the Indonesia Stock Exchange, PT Astra Agro Lestari, Tbk. The data used are secondary data from the company's annual report 2015. The results showed that the application of PSAK 69 led to the recognition of a gain or loss which cannot be realized because of biological assets are not intended for sale. Conclusions from this research is that there is a significant difference on the accounting treatment for biological assets between PSAK 16 and PSAK 69. Â  Keywords: PSAK 69, Fair Value, Biological Assets, Agriculture